Job Retention by People With Disabilities: A Qualitative Study of the Perspectives of People With Multiple Sclerosis - Ponzio, Michela; Pignattelli, Elena; Verri, Anna; Grange, Erica; Persechino, Benedetta; Vitturi, Bruno Kusznir; Bandiera, Paolo; Manacorda, Tommaso; Inglese, Matilde; Durando, Paolo; Battaglia, Mario Alberto (La Medicina del Lavoro, 2024)
Background: Multiple sclerosis (MS), because of its early age at onset, greatly impacts the working lives of those affected by it in ways linked to different factors, both professional and personal. It has been observed that only a small percentage (20-40%) of workers with MS retain their jobs after the diagnosis. When identifying factors determining job retention or loss in this setting, it is essential to consider the direct perspectives of people with MS (PwMS). Methods: A qualitative study, based on the conduction of two focus groups, was conducted to explore the personal experiences of PwMS who work. Results: The results show that there are numerous factors, both positive and negative, that can influence these people’s ability to retain their jobs. The climate established in the workplace and the relationship between workers with MS and their colleagues were fundamentally important aspects, as was knowledge of the disease at the level of public opinion. Conclusions: Managing work is a complex undertaking for people with a disabling condition like MS. There needs to be greater awareness of the employment rights of PwMS. Improving these knowledge-based aspects could undoubtedly improve the quality of the working lives of PwM.